2022
DOI: 10.3389/fgene.2022.833475
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Endangered Dengchuan Cattle Reveals Its Genomic Diversity and Selection Signatures

Abstract: Dengchuan cattle are the only dairy yellow cattle and endangered cattle among Yunnan native cattle breeds. However, its genetic background remains unclear. Here, we performed whole-genome sequencing of ten Dengchuan cattle. Integrating our data with the publicly available data, Dengchuan cattle were observed to be highly interbred than other cattle in the dataset. Furthermore, the positive selective signals were mainly manifested in candidate genes and pathways related to milk production, disease resistance, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…The results show that short ROH segments account for a large proportion (72.29%) in the research population, with an average size of 0.93 Mb. Due to the lower breeding level of local breeds compared to commercial breeds, the proportion of short ROH segments in local breeds was found to be higher than that in commercial breeds [39][40][41]. The two parental rabbit populations in this study had a low probability of inbreeding, which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 89%
“…The results show that short ROH segments account for a large proportion (72.29%) in the research population, with an average size of 0.93 Mb. Due to the lower breeding level of local breeds compared to commercial breeds, the proportion of short ROH segments in local breeds was found to be higher than that in commercial breeds [39][40][41]. The two parental rabbit populations in this study had a low probability of inbreeding, which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 89%
“…After mapping, the “Haplotype Caller”, “Genotype GVCFs” and “Select Variants” modules of the Genome analysis toolkit (GATK, version 3.8-1-0-gf15c1c3ef) [ 15 ] were used to call the SNPs. The mapping and filtering parameters were as shown previously [ 8 ]. SNPs were functionally annotated using ANNOVAR [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies on the genetic diversity and lineage origins of local cattle breeds are becoming more prevalent as the use and price of whole-genome sequencing increase. [ 8 , 9 ]. However, there are no previous studies on Loudi cattle from central Hunan, only research work on Xiangxi cattle from western Hunan has been found [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that worldwide cattle could be divided into five continental groups: European taurine, Eurasian taurine, East Asian taurine, Chinese indicine and Indian indicine (Chen et al, 2018). Nowadays, many reports of indigenous cattle in the Yunnan province have focused on whole-genome sequencing for precise analysis of their genetic features and traits, such as Lincang (Sun et al, 2022), Dengchuan (Jin et al, 2022) and Yunling cattle (Chen, Zhan, et al, 2020). Nevertheless, there is a paucity of literature on genome-wide studies of Zhaotong cattle in the inland regions of Yunnan province.…”
Section: Sc Usmentioning
confidence: 99%